2015
DOI: 10.1016/j.cub.2015.06.058
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Replication Initiation Is Blocked by a Distant Chromosome–Membrane Attachment

Abstract: Summary Although it has been recognized for several decades that chromosome structure regulates the capacity of replication origins to initiate, very little is known about how or if cells actively regulate structure to direct initiation [1–3]. We report that a localized inducible protein tether between the chromosome and cell membrane in E. coli cells imparts a rapid and complete block to replication initiation. Tethers, composed of a trans-membrane and transcription repressor fusion protein bound to an array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…For example, recent work by Magnan et al . showed that chromosome tethering at sites as far as 1 Megabases away from the origin of replication can alter global DNA topology and inhibit replication initiation (Magnan et al ., ). Furthermore, inhibition of gyrase may affect replication initiation indirectly.…”
Section: Discussionsupporting
confidence: 81%
“…For example, recent work by Magnan et al . showed that chromosome tethering at sites as far as 1 Megabases away from the origin of replication can alter global DNA topology and inhibit replication initiation (Magnan et al ., ). Furthermore, inhibition of gyrase may affect replication initiation indirectly.…”
Section: Discussionsupporting
confidence: 81%
“…Since only a single round of replication is triggered by an increase in temperature, topological changes are likely quickly compensated for by adjustments to expression of gyrase and Topo I ( 78 ), implying that net origin energy status is under homeostatic control (below). Similarly, rapidly increasing osmotic levels (to ∼0.5 M NaCl), which results in an immediate but temporary increase in negative supercoiling ( 79 ), induces replication initiation in dnaA46 mutant cells at a restrictive temperature ( 80 ) and also in cells blocked for replication initiation by a chromosome-membrane tether ( 13 ; see also below).…”
Section: Factors That Affect Global Chromosome Structurementioning
confidence: 99%
“…Also, replication initiation in Caulobacter crescentus is regulated through cell cycle changes in chromosome structure and position ( 11 ). It is well established that chromosome condensation in early stationary phase of bacterial growth is highly refractive to initiation of replication and transcription ( 12 ), both of which require duplex melting, and there is emerging evidence that initiation in Escherichia coli is sensitive to chromosome structure changes in the cell cycle ( 13 ). In this review, we outline the key determinants of chromosome structure in bacteria and discuss the role of DNA structure in regulating replication initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that nucleic acid is present in multiple discrete foci is consistent with defects during DNA replication caused by DNA gyrase inhibition (Nakanishi et al, ). The blebs of lipidic material noted along the inside of cells could be related to the tethering of chromosomes to the inner membrane (Magnan & Bates, ; Magnan, Joshi, Barker, Visser, & Bates, ) or could arise from effects on the regulation between peptidoglycan biosynthesis and the timing and completion of DNA replication (Harris & Theriot, ). Previous studies with the other ParE toxin from M. tuberculosis noted bleb formations visible on the cell surface by scanning electron microscopy, consistent with the current observations (Gupta et al, ).…”
Section: Discussionmentioning
confidence: 99%